Development of Nanoemulsion containing Extracts of Ginger (Z. officinale) as Pesticide Eco-friendly - Nur Syafinaz Zulkipli (2018)
The chemical pesticides are widely use in forest plantation and agriculture to protect tree from insect and pest attack. It will contribute to negative impact toward environment such as air pollution, soil pollution and water pollution. The pesticide with nanoemulsion formulation containing essential oil was developed to reduce the usage chemical pesticide. The essential oil ginger was selected because it contains many active compounds. The main aim of this study is to develop the nanoemulsion containing ginger essential oil. Ginger essential oil was prepared by hydrodistillation. The Fourier-transform infrared spectroscopy (FTIR) was used to identify the functional group in ginger essential oil mixed with soybean. The results the functional group formed when ginger essential oil mixed soybean is same. The nanoelmusion based on pseudo-phase ternary diagram from previous study. The ginger essential oil was loaded into soybean oil. The results show that a bluish transparent appearance was formed. The Tyndall effect and Dynamic Light Scattering (DLS) was done to identify the size of nanoemulsion containing ginger essential oil. The nanoemulsion containing ginger essential oil was produced with mean droplet size is 33.95nm. The preliminary test for the effectiveness of nanoemulsion containing essential oil is bioassay test. For bioassay test, only ginger essential oil shows the mortality of ants. This happened due to active ingredients and pungent odor in ginger essential oil. The bioassay test might not be the most suitable for the effectiveness of nanoemulsion containing ginger essential oil.